USE OF EDUCATIONAL AND COGNITIVE TASKS AIMED ON THE FORMATION OF INTELLECTUAL STUDENTS' SKILLS - O.V. Buhriy (Academy of Cognitive and Natural Sciences, 2009)
The article deals with the principal features of a cognitive assignments system. Its influence on formation students' intelligence skills has been revealed.